Pengembangan Sistem Marketplace Bonsai Indonesia Berbasis Web - Januar Komar Ruwanda; Nurudin Santoso; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The Bonsai Community located in Batu City has its own name, the Indonesian Bonsai Fans Community (PPBI). PPBI community which is an organization for bonsai lovers with the aim to preserve bonsai plants. The PPBI community is also usually appointed as the organizer of an event at a bonsai event, such as a race or bonsai trading activity. In a bonsai event, after the competition session a bonsai trading session will be opened, and the community at this session acts as the organizer only allowing a few sellers to sell according to specified conditions and the community also provides a place for sales. Furthermore, a buyer can make purchases and order bonsai that have been selected directly. This activity raises several problems that can disrupt the activities of buying and selling bonsai, including the uncertainty of a buyer in preparing the costs for buying bonsai. If the seller's problem is to have to bring the bonsai directly to be sold to a place of sale that is not necessarily sold. This can be a burden for each party because they have to prepare everything related to the process of buying and selling bonsai. Then a solution to this problem was found that could be taken as a background for conducting this research. In this study also identified to manage the overall process of buying and selling bonsai which will then be implemented with a website platform that focuses on the marketplace using the Laravel framework and with a variety of PHP, HTML and CSS languages. Then a needs analysis has been found with the results of 19 functional needs and only 1 non-functional requirement. The system development carried out by researchers applies a method, namely the Rapid Application Development (RAD) development method, which has several stages, such as business modeling, data modeling, process modeling, application generation and testing. After the developed system has gone through the implementation stage, the system is then tested with several stages, including unit testing and integration with 100% valid results, validation testing with 100% valid results and non-functional testing, namely usability yields a value of 79 which means getting acceptable predicate or this system already meets the needs of users and is suitable for use.